2018
DOI: 10.1111/1755-0998.12771
|View full text |Cite
|
Sign up to set email alerts
|

Double‐digest RAD sequencing outperforms microsatellite loci at assigning paternity and estimating relatedness: A proof of concept in a highly promiscuous bird

Abstract: Information on genetic relationships among individuals is essential to many studies of the behaviour and ecology of wild organisms. Parentage and relatedness assays based on large numbers of single nucleotide polymorphism (SNP) loci hold substantial advantages over the microsatellite markers traditionally used for these purposes. We present a double-digest restriction site-associated DNA sequencing (ddRAD-seq) analysis pipeline that, as such, simultaneously achieves the SNP discovery and genotyping steps and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 72 publications
5
108
1
Order By: Relevance
“…While the fast mutation rate and high polymorphism of microsatellites allow for resolving fine-scale population structuring (Putman & Carbone, 2014), they may be less suitable for inferring genome-wide or individual-level patterns in genetic diversity (Väli, Einarsson, Waits, & Ellegren, 2008), as the number of sampled loci may not be sufficient to represent the total genome of an individual. It has also been demonstrated that SNPs obtained by RADseq produce more precise estimates of relatedness than microsatellites in a range of bird species (Thrasher, Butcher, Campagna, Webster, & Lovette, 2018). Microsatellites may be less efficient for identifying relatives particularly in populations with prior population bottlenecks and lack of gene flow, which limit allelic diversity.…”
mentioning
confidence: 99%
“…While the fast mutation rate and high polymorphism of microsatellites allow for resolving fine-scale population structuring (Putman & Carbone, 2014), they may be less suitable for inferring genome-wide or individual-level patterns in genetic diversity (Väli, Einarsson, Waits, & Ellegren, 2008), as the number of sampled loci may not be sufficient to represent the total genome of an individual. It has also been demonstrated that SNPs obtained by RADseq produce more precise estimates of relatedness than microsatellites in a range of bird species (Thrasher, Butcher, Campagna, Webster, & Lovette, 2018). Microsatellites may be less efficient for identifying relatives particularly in populations with prior population bottlenecks and lack of gene flow, which limit allelic diversity.…”
mentioning
confidence: 99%
“…Paternity was assigned for every offspring from seven calico surfperch broods in COLONY with an error rate of 0.01 following Thrasher et al . (). All broods examined were sired by multiple males.…”
Section: Resultsmentioning
confidence: 97%
“…Utilizing RADseq for paternity assignment is relatively new (Andrews et al ., ; Thrasher et al ., ). The accuracy of paternity assignment utilizing SNPs has been well documented, especially for the use in livestock and fisheries management (Anderson & Garza, ; Fernandez et al ., ; Hauser et al ., ; Jones et al ., ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alternatively, HTS approaches could help to develop a few tens to hundreds of SNPs markers, possibly more efficiently than Sanger sequencing did in the past (Garvin, Saitoh, & Gharrett, 2010). Thrasher, Butcher, Campagna, Webster, and Lovette (2018) used ddRAD to perform relatedness analyses based on 150-600 optimized SNP markers. Other authors characterized small sets of SNP markers to be genotyped through a classical, affordable technology compared to GBS for large numbers of samples (e.g., Ackerman & Campbell, 2012;Westgaard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%